AN INTEGRATIVE QUR'ANIC LEARNING MODEL FOR NAGHAM AL-QUR'AN: A CASE STUDY AT AL-ITTIFAQIAH INDRALAYA ISLAMIC BOARDING SCHOOL - Mudrik Qori; Tobroni; Moh Nurhakim; Diah Karmiyati; Eko Arisandi; Khermarinah (Referensi Islamika: Jurnal Studi Islam, 2026)
Although studies on talaqqi, tahfiz, and Qur’anic learning have expanded considerably, limited attention has been given to explaining nagham learning through an integrated perspective of behaviorism, constructivism, and social learning. This study aims to examine the nagham learning practices at Al-Ittifaqiah Indralaya Islamic Boarding School and to develop a conceptual framework that explains the pedagogical processes underlying students’ tilawah development. This study employed a qualitative case study design. Data were collected through participant observation, in-depth interviews, and document analysis involving five nagham teachers, fifteen students, two pesantren administrators, and three alumni qari. The data were analyzed thematically through coding, categorization, and theme development in accordance with the Standards for Reporting Qualitative Research (SRQR). The findings indicate that nagham learning is organized through six interconnected stages: talaqqi and musyafahah, sima’i, drill, modeling, reflection, and evaluation. These stages support the development of maqamat mastery, aesthetic-spiritual sensitivity (dzauq), and tilawah performance. The learning process reflects the complementary roles of behavioral reinforcement, active knowledge construction, and observational learning within the pesantren environment, where students gradually develop Qur’anic recitation skills through sustained participation in learning activities. This study provides an integrative perspective for understanding nagham learning in Islamic boarding schools by relating traditional instructional practices to contemporary learning theories. However, the findings are derived from a single pesantren, without comparison with other institutions, are based on interpretive qualitative analysis, and do not directly measure students’ tilawah competence. Therefore, the findings should be interpreted within these contextual limitations. This study offers a conceptual framework for interpreting nagham learning as an integrated pedagogical and spiritual process that combines modeling, habituation, reflective learning, and knowledge construction. Unlike previous studies that primarily emphasize talaqqi, tahsin, maqamat mastery, or tilawah performance, the proposed framework explains how these learning processes interact through complementary learning theories within the pesantren context, thereby contributing to discussions on Islamic pedagogy and Qur’anic learning.